THE IMPLEMENTATION OF PARTICIPATION POINT SYSTEM IN A SENIOR HIGH SCHOOL ENGLISH TEACHING - Zakiyah, Pia (2014)
Student's passivity could be seen as a non-involvement from the students to the learning activities in the classroom. When the students are passive, they isolate themselves from the classroom interaction. To motivate the passive students to be active, Participation Point System (PPS) could be implemented as one of the solutions. This research paper was conducted to investigate the implementation of Participation Point System in a senior high school English teaching. This research paper employed a qualitative case study. The participants of this research paper were 35 students of 11th grade in one of senior high school in Bandung. The data were collected through observation, questionnaires and interview. The findings show that the PPS was implemented by the teacher through a series of activities: asking the students' attention; telling the students about the PPS; giving instructions to the students regarding how to participate and get the points; giving the learning materials; giving chances to students to answer and ask questions or share ideas; giving the points after the students participate in the learning activities; and listing the students' participation points in the point list. The PPS was beneficial for the teacher in gaining students' attention, making class atmosphere interesting and interactive, motivating most of the students to be confident in using English and assessing the students' scores. However, it was found that the students had high participation but low cognition, they tended to frequently forget what they had learned even though they were able to apply or review what they had got. Thus, the learning activities were fun but also forgettable. In addition, there were several learning activities the teacher found it difficult to make the low proficiency students to be confident to participate, preparing appropriate questions to be adjusted with the learning material difficulty level and giving an equitable opportunity for all students to participate. Moreover, nearly all of the students responded positively to the PPS implementation. From their perception, the PPS helped them to participate actively, learn English better, enhance their confidence, be more competitive, focus in the learning process, and enrich their vocabulary. However, at the same time they found it difficult in competing with their friends because they have to perform in front of the class with a good English fluency. Keywords: participation points, participation point system, student participation, English teaching. Kepasifan siswa dapat dilihat sebagai ketidakterlibatan siswa di dalam aktivitas pembelajaran di dalam kelas. Ketika siswa pasif, mereka mengisolasi diri mereka dari interaksi kelas. untuk memotivasi siswa yang pasif menjadi aktif. Sistem Poin Partisipasi (PPS) dapat diimplementasikan sebagai salah satu solusinya. penelitian ini dilakukan untuk menginvestigasi implementasi PPS di pengajaran Bahasa Inggris pada jenjang sekolah menengah atas. penelitian ini menggunakan studi kasus dengan metode kualitatif. Partisipan dari penelitian ini adalah 35 siswa kelas 11 di salah satu SMA di Bandung. Data dikumpulkan melalui observasi, kuisioner dan interview. Ditemukan bahwa PPS diimplementasikan oleh guru melalui satu rangkaian aktivitas: meminta perhatian siswa; memberi tahu siswa tentang PPS; memberi instruksi kepada siswa terkait cara untuk berpartisipasi untuk mendapatkan poin; memberikan merti pembelajaran; memberikan kesempatan kepada siswa untuk menjawab dan bertanya atau pun berbagi ide; memberi poin setelah muris berpartisipasi; dan mendaftar poin yang diterima siswa. PPS berguna untuk guru dalam mendapatkan perhatian dari siswa, membuat suasana kelas menjadi menarik dan interaraktif, memotivasi sebagian besar siswa untuk percaya diri dalam menggunakan Bahasa Inggris, dan untuk menilai nilai siswa. Bagaimana pun juga, ditemukan bahwa partisipasi yang tinggi memiliki kemampuan kognisi yang rendah, dalam artian siswa cenderung melupakan apa yang mereka pelajari walaupun mereka mampu menggunakan materi yang mereka dapatkan. Aktivitas pembelajaran menyenangkan tetapi mudah untuk dilupakan. Terdapat beberapa kesulitan bagi guru untuk membuat siswa dengan kemampuan rendah untuk percaya diri berpartisipasi, menyiapkan pertanyaan yang cocok dengan level kesulitan materi, serta memberikan kesempatan yang adil bagi seluruh siswa. Di lain sisi, sebagian siswa merespon positif terhadap implementasi PPS. PPS menolong mereka untuk aktif berpartisipasi, belajar Bahasa Inggris lebih baik, meningkatkan percaya diri, lebih konpetitif, fokus dalam proses pembelajaran, dan memperkaya kosa kata. Di saat yang sama mereka merasa kesulitan untuk berkompetisi dengan rekannya karena mereka harus tampil di depan kelas dengan Bahasa Inggris yang fasih.